Delays in treatment initiation for patients with relapsing-remitting multiple sclerosis—A nationwide population-based study - Savolainen, Maiju; Viitala, Matias; Kuutti, Katariina; Kuusisto, Hanna; Rauma, Ilkka; Ryytty, Mervi; Krüger, Johanna; Hartikainen, Päivi; Niiranen, Marja; Saarinen, Jukka; Soilu-Hänninen, Merja; Laakso, Sini M (SAGE Publications, 2026)
Background
Early disease-modifying therapy (DMT) improves outcomes in patients with relapsing-remitting multiple sclerosis (pwRRMS), but reasons for delayed or absent initiation are unclear.
Objective
To investigate reasons and trends for delayed or absent DMT initiation among Finnish pwRRMS.
Methods
A nationwide retrospective study using the Finnish MS Registry identified 2363 pwRRMS diagnosed between 2010 and 2019 in the participating centers. Patients never receiving DMT or starting >2 years post-diagnosis were compared to those initiating DMT within a year of diagnosis.
Results
We identified 193 pwRRMS who never started DMT, 88 had delayed initiation over 2 years, and 1944 started within a year. The no/delayed DMT group was older at diagnosis (mean 38.7 vs 35.2 years, p < 0.001). Corticosteroid-treated relapses were more frequent among early initiators. Optic neuritis was more common in patients with delayed or no DMT. Treatment refusal was the primary reason for delayed/no DMT (35.6%), with 68% of refusers never starting. From 2010to 2019, delayed/no DMT initiation (p = 0.007) and treatment refusal (p = 0.004) decreased significantly.
Conclusion
Delayed or absent DMT initiation is linked to older age, optic neuritis, disease inactivity, and treatment refusal, which declined over time, likely due to expanded DMT options.